The role of parliamentarians in promoting self-care interventions for sexual and reproductive health and rights: applying COVID-19 lens in the Eastern Mediterranean region - Hala Abou-Taleb; Nada Mohamed; Karima Gholbzouri; Elisa Scolaro; Inaya Ezzeddine; Souhail Alouini; Heba Hagrass; Magdy Morshed; Neil Datta (BMC, 2021)
Abstract Innovative people-centered care modalities including self-care interventions offer an opportunity to ensure continuity of healthcare services during COVID-19 and in post-COVID-19, as well as contribute to the achievement of universal health coverage. Parliamentarians are uniquely positioned to promote self-care interventions for sexual and reproductive health and rights through their legislative, budget allocation, oversight, and advocacy roles. However, existing health systems governance challenges in the Eastern Mediterranean region such as weak institutions setups, fragmentation of health programs, and limitation of resources could impede parliamentarians' progress. To address these challenges, the following recommended actions should be considered: (1) promote the adaptation of sexual and reproductive health and rights service packages at primary healthcare level to integrate self-care interventions (2) govern innovative people-centered care channels including self-care interventions; and (3) engage in a dialogue with civil society and communities to meet needs, raise public awareness and generate demand.